Does urban sprawl rejuvenate the suburban village? A study of rural communities neighbouring Olsztyn - Źróbek-Różańska, Alina; Zysk, Elżbieta (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
This article addresses the question of whether urban sprawl, apart from changing the spatial conditions, rejuvenate the Polish suburban village This has involved the analysis of internal migration tendencies in Poland followed by an in-depth analysis of communities (gminas) in the neighbourhood of Olsztyn, the provincial capital of Warmia and Mazury. For this study the data sources were used mainly from the Main Statistical Office (GUS) and the Public Opinion Research Centre (CBOS). This data was supplemented by information gathered in a questionnaires in order to complete a full overview of the described process and to provide precisely expectations in the nearest future. The results have been presented to show the opinions and residential plans of people divided into two age groups: “juniors” and “seniors”.
Keywords: migrations; rural areas; urban sprawl